CARBON STOCK ESTIMATION ON REPONG DAMAR LANDSCAPE IN PESISIR BARAT REGENCY, LAMPUNG PROVINCE - Oktavian Rizky Risnanda; Indra Gumay Febryano; Arief Darmawan; Rudi Hilmanto; Intan Nurhajah (Jurnal Belantara, 2026)
Climate change mitigation activities in the forestry sector are currently widely carried out through the REDD+ scheme, especially in tropical regions. In the REDD+ scheme, information on forest carbon stocks in areas used as REDD+ activity locations will be essential. This study aims to estimate aboveground carbon stocks in the damar repong landscape in Pesisir Barat Regency, Lampung Province, which consists of three main land cover types, namely repong damar, natural forest, and mixed gardens. The approach used is a non-destructive method with a purposive sampling technique on 42 sample plots. Vegetation data were collected by measuring the diameter, height, and density of wood, then biomass was calculated using allometric equations and converted into carbon stocks. The results showed that the highest average carbon stock was found in repong damar at 269.74 tC/ha, followed by natural forest at 167.01 tC/ha, and mixed gardens at 96.61 tC/ha. Variations in carbon stocks in the three land covers were influenced by stand structure, tree size, and vegetation density. Statistical analysis showed the highest level of uncertainty in natural forest and the lowest in mixed gardens. This study confirms that traditional agroforestry systems such as damar repong have significant potential in mitigating climate change through high carbon storage.